CARDIOPROTECTIVE EFFECT OF FISETIN ON LYSOSOMAL ENZYME ACTIVITIES OF NORMAL AND ISOPROTERENOL-INDUCED MYOCARDIAL INFARCTION IN MALE WISTAR RATS - PANNEERSELVAM, MYTHILY; P. T, DEVIKA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to evaluate the cardioprotective effect of fisetin on change in the activities of lysosomal enzymes in isoproterenol (ISO)- induced myocardial infarction (MI) in male albino Wistar rats. Methods: Rats were orally pretreated with fisetin (30 mg/kg body weight) daily for 30 days. After the pretreatment period, ISO (100 mg/kg body weight) was subcutaneously administered to rats at intervals of 24 h for 2 consecutive days. Results: The activities of β-glucuronidase, β-N-acetylglucosaminidase, β-galactosidase, cathepsin-B, and cathepsin-D were significantly (*p<0.05) increased in serum and the heart of ISO-induced rats. Pre-treatment with fisetin daily for 30 days to ISO-induced rats significantly prevented these activities and restored their activities to near normal. Oral treatment with fisetin (30 mg/kg body weight) to normal control rats did not show any significant effect. Conclusion: We have concluded that fisetin protects the β-glucuronidase, β-N-acetylglucosaminidase, β-galactosidase, cathepsin-B, and cathepsin-D against ISO-induced MI. The observed effects might be due to the free radical-scavenging and membrane-stabilizing effect of fisetin.